Clinical features and management of women with Mayer-Rokitansky-Küster-Hauser syndrome in a Thai population - Phawat Matemanosak; Krantarat Peeyananjarassri; Satit Klangsin; Saranya Wattanakumtornkul; Kriengsak Dhanaworavibul; Chainarong Choksuchat; Chatpavit Getpook (Korean Society of Obstetrics and Gynecology, 2024)
Objective This study aimed to describe the clinical features, associated extragenital anomalies, and management of Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome in a Thai population. Methods This retrospective study analyzed the medical records of 96 patients with MRKH syndrome diagnosed and treated at a university hospital and tertiary referral center in southern Thailand between 2000 and 2022. Results The study included 96 patients with MRKH syndrome. The most common symptom was primary amenorrhea (88.5%), followed by difficulty or inability to engage in sexual intercourse (9.4%) and pelvic mass (2.1%). Notably, 80.3% of the patients did not have extragenital malformations and were diagnosed with MRKH type I (typical form), whereas 19.7% were categorized as MRKH type II (atypical form). Skeletal malformations were the most frequent extragenital anomalies and were present in 19.5% of patients, with scoliosis being the most common skeletal condition. Other extragenital malformations included renal (8.5%) and neurological (1.0%) abnormalities. Clinical vaginal examination revealed complete atresia in 21.8% and vaginal hypoplasia (median vaginal length, 3 cm) in 78.2% of the patients. Half of the patients did not receive treatment because they had not engaged in sexual intercourse. In this cohort, 41.7% of the patients had no difficulty performing sexual intercourse. Hence, self-dilation therapy or concomitant dilation was recommended. Only eight patients (8.3%) underwent surgical reconstruction of the vagina. Conclusion This study confirmed the complexity and heterogeneity of the phenotypic manifestations of MRKH, including the degree of vaginal atresia and types and rates of associated malformations.